Pekerjaan Mulia dalam Perspektif Al-Quran - Miskahuddin, Miskahuddin (Jurnal Ilmiah Al-Mu'ashirah: Media Kajian Al-Qur'an dan Al-Hadits Multi Perspektif, 2021)
Work is an obligation for every Muslim who believes in Allah S.W.T. The Qur'an regulates and encourages people to work optimally and correctly in order to get halal and good sustenance to support themselves and their families. The noble work referred to in the Qur'an is a useful job, providing income and profits to meet the external and internal needs of humans so that they are strong in worship to Allah S.W.T in accordance with their abilities. The essence of a noble job in the Qur'an perspective is a pure and lawful job that is legal according to religion when a person gets sustenance and is used sparingly and carefully, not extravagantly and redundantly and adapted to the basic necessities of life as a man who believes and fear Allah SWT.ABSTRAKPekerjaan adalah kewajiban bagi setiap muslim yang beriman kepada Allah S.W.T. Al-Qur’an mengatur dan mendorong manusia untuk bekerja secara maksimal dan benar guna mendapatkan rezeki yang halal dan baik untuk menafkahkan diri maupun keluarganya. Pekerjaan mulia yang dimaksud Al-Quran tentu saja merupakan pekerjaan yang bermanfaat dan berguna memberikan penghasilan dan keuntungan untuk memenuhi kebutuhan lahiriah dan bathiniah manusia agar kuat melaksanakan ibadah kepada Allah S.W.T sesuai dengan kesanggupan dan kemampuan hamba Allah itu sendiri. Hakikat pengertian pekerjaan yang mulia dalam perspektif Al-Qur’an adalah suatu pekerjaan murni dan halal yang sah menurut agama manakala seseorang mendapatkan rezeki dan dipergunakan secara hemat dan cermat, tidak boros dan mubazir serta disesuaikan dengan pokok-pokok keperluan hidup sebagai manusia yang beriman dan bertaqwa kepada Allah S.W.T